THE INVESTIGATION OF RELATIONSHEEP OF TYPOLOGICAL FEATURES AND DECISION-MAKING STRATEGIES AT MANAGERS - Papoyan , V.R.; Tonikyan, T.G. (Modern Psychology, 2020)
The strategies and typological features of decision making were studied among middle managers at different stages of professional development. The significant role of the “vigilance” strategy at different stages of managerial activity is shown. It was found that the importance of the emotional component in the decision-making process decreases while enhancing the logical and informed choice in making decisions.